2005
DOI: 10.1161/01.str.0000155688.18207.33
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the PHQ-9 as a Screening Tool for Depression After Stroke

Abstract: Background and Purpose-The purpose of this study was to examine the performance of the Patient Health Questionnaire (PHQ)-9, a 9-item depression scale, as a screening and diagnostic instrument for assessing depression in stroke survivors. Methods-As part of a randomized treatment trial for poststroke depression (PSD), subjects with and without PSD completed the PHQ-9, a 9-item summed scale, with scores ranging from 0 (no depressive symptoms) to 27 (all symptoms occurring daily). Subjects endorsing 2 or more sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
275
2
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 327 publications
(294 citation statements)
references
References 33 publications
(28 reference statements)
8
275
2
7
Order By: Relevance
“…Consistent with previous research 58,[76][77][78] , the PHQ-2 demonstrated very good operating characteristics. The best cutoff point for sensitivity and specificity (≥3) provided very high specificity for any depressive disorder, an advantage in primary care and resource-constrained HIV clinics, where low specificity creates a problem by generating many false positives.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with previous research 58,[76][77][78] , the PHQ-2 demonstrated very good operating characteristics. The best cutoff point for sensitivity and specificity (≥3) provided very high specificity for any depressive disorder, an advantage in primary care and resource-constrained HIV clinics, where low specificity creates a problem by generating many false positives.…”
Section: Discussionsupporting
confidence: 90%
“…The Patient Health Questionnaire-9 (PHQ-9) is the only validated instrument 11,46 that focuses on the nine diagnostic criteria for DSM-IV depressive disorders and is very brief 53 , an advantage in resource-constrained Kenyan clinics. The PHQ-9 can be self-administered 53,54 or interviewer-administered 11,55,56 , and is well validated in the US as a dual-purpose instrument that yields both a measure of depression severity 57,58 and criteria-based diagnoses of DSM-IV depressive disorders 53,54 : major depressive disorder (MDD), other depressive disorder (ODD) and any depressive disorder (i.e., MDD or ODD).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations